Dynamics of classical wave scattering by small obstacles - FERREIRA, MAURO (American Physical Society, 2001)
A causality problem in the time-dependent scattering of classical waves from point scatterers is pointed out and analyzed. Based on an alternative model, the leading pole approximation of the exact scattering matrix of the square-well potential, transparent expressions for the time- and position-dependent Green function in a disordered medium are derived.
PUBLISHED
Keywords: Physics